Manufacturing Approaches of New Halogenated Agrochemicals. Issue 12 (17th February 2022) - Jeschke, Peter
Abstract: To ensure sustainability, the agrochemical industry is faced with enormous challenges, from provision of high‐quality food to water use, environmental impact and growing world population. The loss of agrochemicals due to consumer perception, changing grower needs and everchanging regulatory requirements is higher than the number of active ingredients being introduced into the market. Therefore, the development of new agrochemicals is essential, that can provide improved efficacy and favorable environmental profiles. In this context, introduction of halogen atoms into a molecule is an important tool to influence its physico‐chemical properties. Since 2010, around 81 % of the launched agrochemicals contain halogen atoms. This Review gives an overview of the latest generation of halogen‐containing agrochemicals introduced into the market over the past 10 years and describes manufacturing approaches of current halogen‐containing development candidates. Abstract : An overview of the latest generation of halogen‐containing agrochemicals introduced into the market over the past 10 years is provided. Manufacturing approaches of current halogen‐containing development candidates are described.